Qiang Xin 1 Formula Suppresses Excessive Pro-Inflammatory Cytokine Responses and Microglia Activation to Prevent Cognitive Impairment and Emotional Dysfunctions in Experimental Sepsis - Wang, Xuerui; Xu, Xiaolong; Guo, Yuhong; Huang, Po; Ha, Yanxiang; Zhang, Rui; Bai, Yunjing; Cui, Xuran; He, Shasha; Liu, Qingquan (Frontiers in Pharmacology, 2020)
Sepsis commonly leads to acute and long-term cognitive and affective impairments which are associated with increased mortality in patients. Neuroinflammation characterized by excessive cytokine release and immune cell activation underlies the behavioral changes associated with sepsis. We previously reported that the administration of a traditional Chinese herbal Qiang Xin 1 (QX1) formula improves survival in septic mice. This study was performed to better understand the effects and the mechanisms of QX1 formula treatment on behavioral changes in a preclinical septic model induced by cecal ligation and puncture. Oral administration of QX1 formula significantly improved survival, alleviated overall cognitive impairment and emotional dysfunction as assessed by the Morris water maze, novel object recognition testing, elevated plus maze and open field testing in septic mice. QX1 formula administration dramatically inhibited short and long-term excessive pro-inflammatory cytokine production both peripherally and centrally, and was accompanied by diminished microglial activation in septic mice. Biological processes including synaptic transmission, microglia cell activation, cytokine production, microglia cell polarization, as well as inflammatory responses related to signaling pathways including the MAPK signaling pathway and the NF-κB signaling pathway were altered prominently by QX1 formula treatment in the hippocampus of septic mice. In addition, QX1 formula administration decreased the expression of the M1 phenotype microglia gene markers such as Cd32, Socs3, and Cd68, while up-regulated M2 phenotype marker genes including Myc, Arg-1, and Cd206 as revealed by microarray analysis and Real-time PCR. In conclusion, QX1 formula administration attenuates cognitive deficits, emotional dysfunction, and reduces neuroinflammatory responses to improve survival in septic mice. Diminished microglial activation and altered microglial polarization are involved in the neuroprotective mechanism of QX1 formula.